A comprehensive substance flow analysis of a municipal wastewater and sludge treatment plant. (November 2015) - Yoshida, H.; Christensen, T.H.; Guildal, T.; Scheutz, C.
Highlights: Substance flow analysis was conducted at a municipal wastewater treatment plant. Fate of TOC and 32 inorganic constituents was identified at the unit process level. Conventional treatment process found to reduce toxic potential of wastewater. Abstract: The fate of total organic carbon, 32 elements (Al, Ag, As, Ba, Be, Br, Ca, Cd, Cl, Co, Cr, Cu, Fe, Hg, K, Li, Mg, Mn, Mo, N, Na, Ni, P, Pb, S, Sb, Se, Sn, Sr, Ti, V, and Zn) and 4 groups of organic pollutants (linear alkylbenzene sulfonates, bis(2-ethylhexyl)phthalate, polychlorinated biphenyl and polycyclic aromatic hydrocarbons) in a conventional wastewater treatment plant were assessed. Mass balances showed reasonable closures for most of the elements. However, gaseous emissions were accompanied by large uncertainties and show the limitation of mass balance based substance flow analysis. Based on the assessment, it is evident that both inorganic and organic elements accumulated in the sewage sludge, with the exception of elements that are highly soluble or degradable by wastewater and sludge treatment processes. The majority of metals and metalloids were further accumulated in the incineration ash, while the organic pollutants were effectively destroyed by both biological and thermal processes. Side streams from the sludge treatment process (dewatering and incineration) back to the wastewater treatment represented less than 1% of the total volume entering the wastewater treatment processes, but represented significant substance flows. In contrast, the contribution by spent water from the flue gas treatment process was almost negligible. Screening of human and eco-toxicity by applying the consensus-based environmental impact assessment method USEtox addressing 15 inorganic constituents showed that removal of inorganic constituents by the wastewater treatment plant reduced the toxic impact potential by 87–92%.